Assessment of Folic Acid Supplementation in Pregnant Women by Estimation of Serum Levels of Tetrahydrofolic Acid, Dihydrofolate Reductase, and Homocysteine - Manisha Naithani; Vartika Saxena; Anissa Atif Mirza; Ranjeeta Kumari; Kapil Sharma; Jyoti Bharadwaj (Scientifica)
Background. Status of folic acid use in pregnant women of the hilly regions in North India was little known. This study was carried out to assess the folic acid use and estimate folate metabolites in pregnant women of this region. Materials and Methods. This cross-sectional study is comprised of 76 pregnant women, whose folic acid supplementation was assessed by a questionnaire and serum levels of homocysteine, tetrahydrofolic acid (THFA), and dihydrofolate reductase (DHFR) were estimated using Enzyme Linked Immunoassays. Results. The study data revealed awareness of folic acid use during pregnancy was present in 46.1% and 23.7% were taking folic acid supplements. The study depicted that there was no statistically significant difference between serum levels of THFA and DHFR in pregnant women with and without folic acid supplements (p=0.790). Hyperhomocysteinemia was present in 15.78% of the participants. Conclusion. Less awareness about folic acid supplementation and low use of folic acid by pregnant women were observed in this region. Sufficient dietary ingestion may suffice for the escalated requirements in pregnancy, but since this cannot be ensured, hence folic acid supplementation should be made as an integral part of education and reproductive health programs for its better metabolic use, growth, and development of fetus.